Elementary statistic for sciences with SPSS - Ling, Teck Yee; Hong, Kian Sam (Universiti Malaysia Sarawak, 2012)
With the widespread of availability of computers and statistical software and the application of quantitative methods in many fields of studies, introductory statistical course now emphasizes statistical reasoning more than computational skill development. Questions of how have given way to questions of why, when and what? The goal of this book is to enable users to work independently, learning software skills while coming to understand the underlying statistical concepts and techniques.